A continuum mechanics model of multi-buckling in graphene – substrate systems with randomly distributed debonding. (15th October 2016) - Gao, Xiguang; Li, Chunyu; Song, Yingdong; Chou, Tsu-Wei
Highlights: A continuum mechanics model of multi-buckling in graphene is proposed. The effect of randomly distributed interfacial debonding is considered. The mechanism of compression-induced multi-buckling in graphene is revealed. Stronger adhesive stress leads to more uniformly distributed buckles. Estimating the interfacial interactions by the present method. Abstract: The wrinkling morphology resulted from the multi-buckling process of graphene sheet supported on a PDMS substrate is modeled by a continuum mechanics approach. The effects of randomly distributed interfacial debonded regions as well as adhesive and shear stresses between graphene sheet and substrate are considered. The buckling process has been examined. The present approach reveals the mechanism of multi-buckling in graphene sheet supported by an elastic substrate and can simulate the initiation, growth and saturation of the buckles. The value of adhesive stress controls the morphology of buckling in graphene. Higher values of adhesive stress lead to more uniformly distributed buckles with tiny sizes while lower values lead to large buckle sizes. This study also has demonstrated the capability in estimating the interfacial shear strength and adhesive stress. Graphical abstract: